Long-Term Oncological Outcomes of Papillary Thyroid Cancer and Follicular Thyroid Cancer in Children: A Nationwide Population-Based Study - van de Berg, Daniël J.; Kuijpers, Anke M. J.; Engelsman, Anton F.; Drukker, Caroline A.; van Santen, Hanneke M.; Terwisscha van Scheltinga, Sheila C. E. J.; van Trotsenburg, A. S. Paul; Mooij, Christiaan F.; Vriens, Menno R.; Nieveen van Dijkum, Els J. M.; Derikx, Joep P. M. (Frontiers in Endocrinology, 2022)
Abstract Introduction Pediatric thyroid carcinoma is a rare malignancy and data on long-term oncological outcomes are sparse. The aim of this study was to describe the long-term oncological outcomes of pediatric papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC) in a national cohort, and to identify risk factors for recurrence. Methods We conducted a nationwide, retrospective cohort study, in which we combined two national databases. Patients aged <18 years, diagnosed with PTC or FTC in the Netherlands between 2000 and 2016, were included. pT-stage, pN-stage, multifocality and angioinvasion were included in a Cox-regression analysis for the identification of risk factors for recurrence. Results 133 patients were included: 110 with PTC and 23 with FTC. Patients with PTC most often presented with pT2 tumors (24%) and pN1b (45%). During a median follow-up of 11.3 years, 21 patients with PTC developed a recurrence (19%). Nineteen recurrences were regional (91%) and 2 were pulmonary (9%). No risk factors for recurrence could be determined. One patient who developed pulmonary recurrence died two years later. Cause of death was not captured. Patients with FTC most often presented with pT2 tumors (57%). One patient presented with pN1b (4%). In 70%, no lymph nodes were collected. None of the patients with FTC developed a recurrence or died. Conclusion Pediatric PTC and FTC are two distinct diseases. Recurrence in pediatric PTC is common, but in FTC it is not. Survival for both pediatric PTC and FTC is very good.